Impact of document type on reporting quality of clinical drug trials: a comparison of registry reports, clinical study reports, and journal publications. (3rd January 2012) - Wieseler, Beate; Kerekes, Michaela F; Vervoelgyi, Volker; McGauran, Natalie; Kaiser, Thomas
Abstract : Objective To investigate to what extent three types of documents for reporting clinical trials provide sufficient information for trial evaluation. Design Retrospective analysis Data sources Primary studies and corresponding documents (registry reports, clinical study reports, journal publications) from 16 health technology assessments of drugs conducted by the German Institute for Quality and Efficiency in Health Care between 2006 and February 2011. Data analysis We assessed reporting quality for each study and each available document for six items on methods and six on outcomes, and dichotomised them as "completely reported" or "incompletely reported." For each document type, we calculated the proportion of studies with complete reporting for methods and outcomes, per item and overall, and compared the findings. Results We identified 268 studies. Publications, study reports and registry reports were available for 192 (72%), 101 (38%), and 78 (29%) studies, respectively. Reporting quality was highest in study reports, which overall provided complete information for 90% of items (1086/1212). Registry reports provided more complete information on outcomes than on methods (overall 330/468 (71%) v 147/468 (31%)); the same applied to publications (594/1152 (52%) v 458/1152 (40%)). In the matched pairs analysis, reporting quality was poorer in registry reports than in study reports for overall methods and outcomes (P<0.001 in each case). Compared with publications, reporting quality was poorer in registry reports for overall methods (P<0.001), but better for outcomes (P=0.005). Conclusion Registry reports and publications insufficiently report clinical trials but may supplement each other. Measures to improve reporting include the mandatory worldwide implementation of adequate standards for results registration.